Beyond the Algebra of Explanation: HOV for the Technology Age - Trefler, Daniel; Zhu, Susan Chun (American Economic Review, 2000)
It is hard to believe that factor-endowments theory could offer an adequate explanation of international trade patterns. While the theory adequately predicts Saudi Arabian oil exports, it hardly seems appropriate for explaining the revolutionary impact of new technologies on world trade. Yet to take this position is to misunderstand the thrust of recent empirical research in international trade, research that is giving shape to a new generation of Heckscher-Ohlin-Vanek (HOV) thinking. The core of this new thinking is a class of HOV predictions that allow for international differences in technology and choice of techniques. The literature is in the process of rapid evolution. As a result, the key questions tend to get lost. There have been three of them. First, what empirical regularities account for the poor performance of the HOV model? Second, are there alternative assumptions about technology that lead to better test results for the model? Both of these are interesting questions, but they hardly constitute an end point for understanding the impacts of international trade. As Edward E. Leamer (1993 p. 439) pointed out, [E]conomists ought to abandon the idea that models are either true or false in favor of the notion that models are sometimes useful and sometimes misleading. The third and most important question is whether the HOV model provides a useful framework for thinking about international technology differences. In spite of the defects of the model, the answer is a definite ''yes.9